IPEX as a Consequence of Alternatively Spliced FOXP3 - Mailer, Reiner K. (Frontiers in Pediatrics, 2020)
The transcription factor FOXP3 controls the immunosuppressive program in CD4+ T cells that is crucial for systemic immune regulation. Mutations of the single X-chromosomal FOXP3 gene in male individuals cause the inherited autoimmune disease immune dysregulation, polyendocrinopathy, enteropathy, and X-linked (IPEX) syndrome. Insufficient gene expression and impaired function of mutant FOXP3 protein prevent the generation of anti-inflammatory regulatory T (Treg) cells and fail to inhibit autoreactive T cell responses. Diversification of FOXP3 functional properties is achieved through alternative splicing that leads to isoforms lacking exon 2 (FOXP3Δ2), exon 7 (FOXP3Δ7), or both (FOXP3Δ2Δ7) specifically in human CD4+ T cells. Several IPEX mutations targeting these exons or promoting their alternative splicing revealed that those truncated isoforms cannot compensate for the loss of the full-length isoform (FOXP3fl). In this review, IPEX mutations that change the FOXP3 isoform profile and the resulting consequences for the CD4+ T-cell phenotype are discussed.